A PERCLOS-based Driver Fatigue Detection based Driver Fatigue Detection - Kamarul Hawari, Ghazali; Jie, Maa; Rui, Xiao (2012)
Drowsy driving is a major reason, though elusive, triggering traffic crashes according recently investigation result. Image processing is a kind of multi-dimension signal processing. With the development of semiconductor integrated circuit, image processing technology has been used in multifarious fields. In this paper, an approach based image processing, was proposed.to detect driver's status behind wheel. The target of the proposed approach is to avoid vehicle accident causing by driver fatigue and to improve vehicle safety. According the result of experimental work, the proposed approach is effective for increasing safe in drive